Revisions and updates to the Everyday Cognition (ECog) scales: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Farias, Sarah Tomaszewski; Huss, Olivia; Chan, Michelle L.; Ruiz, Rene
Abstract: Background: Accurate and reliable assessment of everyday functional abilities among older adults is important in clinical and research settings. The Everyday Cognition scale (ECog) was designed over a decade ago to measure early everyday functional limitations across multiple domains: Everyday Memory, Language, Visuospatial Abilities, Planning, Organization, and Divided Attention. The ECog has been shown to be sensitive to early detection of neurodegenerative disease such as Alzheimer's, and in tracking disease progression. The goal of the current study was to update the content of the ECog and ensure its culturally applicable to diverse older adult populations. Method: 42 individuals were included in the study. Participants included older adults with and without Mild Cognitive Impairment (MCI) and their informants/study partners. 66% of the sample was of an ethnic minority. We utilized iterative cognitive interviewing methods to examine the understandability and cultural relevance/applicability of ECog items. This information was then used to modify existing items, delete poor items, and develop new items as needed. Two rounds of interviews were completed with older adults and informants. The purpose of Round 1 was to inform the revision of existing items and elicit new items. The purpose of Round 2 was to confirm the understandability of items revised or produced from Round 1. All interviews were transcribed verbatim and analyzed using standard qualitative methods. Result: Based on analysis of interview feedback, instructions to the ECog were modified slightly to emphasize current performance is being compared to an individual's own baseline level of function. Response options remained primarily unchanged from the original version. When evaluating each of the individual items, participant feedback lead to 15 of the 39 original items being revised to improve item clarity and understandability. A total of 4 items were deleted;3 due to outdated content (e.g., using a map, balancing a checkbook) and 1 because it was vague. A total of 6 entirely new items were developed, primarily to cover more contemporary activities (e.g., use of technology). Conclusion: The final revised ECog includes 41 items. Future work will validate the revised ECog by measuring it in association with neuropsychological performance, external measures of disease, and other functional measures.